Evaluation of Proficiency Test Preparation Course Program at the Language Laboratory of FKIP-UGN - Yulia Rizki Ramadhani; Ambiyar Ambiyar; Ishak Aziz (Universitas Muhammadiyah Kalimantan Timur, 2023)
This study uses the Kirkpatrick evaluation model to evaluate the implementation of the Proficiency Test Preparation Course Program at the UGN FKIP Language Laboratory. This research is qualitative and quantitative descriptive research, with the type of research used evaluative research. The subjects of this study were 30 students who attended language training from various study programs at Universitas Graha Nusantara. The instrument used is a questionnaire with a Likert scale, a formal test through pre-test and post-test. Data analysis was carried out by drafting, classification, processing, interpretation and conclusion. The results show that the Proficiency Test Preparation Course Program, run at the Language Laboratory of FKIP UGN, can be continued because it helps non-English Department students develop foreign language competence. The results of this evaluation can be used as material for consideration in determining steps that can be taken to improve the implementation of the Proficiency Test Preparation Course Program so that the results of this program can be achieved optimally.